The Estimation of Capital Consumption in National Accounting - Stuvel, G. (Review of Economic Studies, 1955)
Journal Article The Estimation of Capital Consumption in National Accounting Get access G. Stuvel G. Stuvel Paris Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 3, 1955, Pages 181–192, https://doi.org/10.2307/2295723 Published: 01 December 1955